ENERGY EFFICIENCY ARCHITECTURE OF WATER PACKAGING INDUSTRY DEVELOPMENT ON PT SWABINA GATRA DISTRICT GRESIK - habibah, umi; Setiyowati, Ernaning; Kurnawaty, Prima (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green Technology, 2017)
In Surah Az-Zumar 21 explained that God had given a lot of resources on earth for the welfare of the creatures. God provides humans to take advantages of all the blessing things that exist properly and not forget to be grateful for it. Everything has been available on the earth for human life. The source of natures is very abundant such as water. Conservation and consumption of the water can be used in the form of treatment of drinking water in the packaging. Application of drinking water in daily life is good for people’s health, whereas groundwater sources have been contaminated by waste and drinking water consumption have impacts on human life. One of the cities that implement the processing of drinking water is Gresik city in the company of PT Gresik “Swabina Gatra”. PT Swabina Gatra was 26 years old, has been managing drinking water which is capable of producing drinking water of seventy thousand units per month in the form of cups, bottles, and gallon. The production will be increased to 150 thousand units per month. The big concern of public for consuming drinking water alter increasing of production capacity. Thus, PT Swabina Gatra will develop the drinking water industry. The drinking water industry development is applying the theme of energy efficiency in architecture because it involves consideration of the location, cost, machinery and labor and energy efficient building design. Energy efficiency in architecture is trying to minimize energy usage without limiting the user’s needs and activities. Thus the building will reduce expenses in drinking water industry development and provide positive impacts to the environment around.